The Role of Blockchain Technology in the Development of Accounting in Iran - Javan , Saeed; Maranjory, Mehdi; Alikhani , Razieh; Fallah , Reza (Business, Marketing, and Finance Open, 2026)
The purpose of the present study is to propose a model of the drivers and barriers of blockchain technology influencing the development of accounting. A mixed-methods approach combining qualitative (grounded theory) and quantitative phases was employed. In the qualitative phase, using the snowball sampling method, semi-structured interviews were conducted with 17 experts and specialists in the fields of accounting and information technology in Iran, and data were collected until theoretical saturation was achieved. Data analysis through open, axial, and selective coding led to the identification of 55 concepts and 12 categories. The identified categories in this phase included political, social, legal, environmental, technological, and economic drivers, as well as political, social, legal, environmental, technological, and economic barriers. In the quantitative phase, a questionnaire was developed based on the conceptual model and distributed among 329 accountants and auditors who were members of the Iranian Association of Certified Public Accountants, as well as experts and managers in the field of financial technologies in fintech companies. The results obtained from the Interpretive Structural Modeling (ISM) indicated that among the blockchain drivers, the most influential factors were economic drivers, followed by social and environmental drivers. Finally, technological, legal, and political drivers were identified as the most influenced ones. Moreover, the findings related to blockchain barriers revealed that the most influential barriers were political, followed by social, environmental, and technological ones. The most influenced barriers were legal and economic. The findings of this study can be beneficial for managers and policymakers in the accounting and auditing sectors in effectively implementing blockchain-based programs.